SYNTHESIS OF ALUMINIUM AND COBALT SUBSTITUTED LITHIUM FERRITE BY STANDERD CERAMIC METHOD (Global Journal of Advanced Engineering Technologies and Sciences, 2016)
A recent literature survey of magnetoplumbite (M- type ) ferrite, Lithium hard ferrites with Aluminium and Cobalt substituted samples with the general chemical formula Li0.5Fe0.5+xCoxAl12-2X O19 were synthesized using reacting oxide by high temperature solid state reaction technique. The structural characterization of compound has been carried out from X-Ray diffraction powder pattern. The compounds are in single hexagonal phase without traces of uncertainly ambiguous reflection. From XRD pattern lattice parameters has recorded with increasing doped aluminium element in the range from a = 5.807 Å to 5.906 Å and c = 22.507 Å to 22.585 Å pertaining the space group P63/mmc (No.194) conformed from JCPDS data. The mass density of the ferrites were found linearly varies and depends upon the mass and volume of sample. The X-Ray density has depends upon the lattice constant and molecular weight of the compounds. The average particle size was also estimated. The compounds were studies magnetically by using Guoy’s method in the temperature range 300 to 800 K, the result shows that the compounds are paramagnetic in nature. The Curie molar constant was work out.